The world book student discovery encyclopedia P.Q.R (Volume 9) - World Book, Inc (Chicago: World Book, 2005)
A general elementary encyclopedia with brief illustrated articles covering an alphabetical array of topics
Keywords: encyclopedias, Children's encyclopedias and dictionaries